H2O on Si(001): surface optical anisotropy from first-principles calculations - Seino, K.; Schmidt, Wolf Gero (Surface Science)

Ground- and excited-state properties of DNA base molecules from plane-wave calculations using ultrasoft pseudopotentials - Preuss, M.; Schmidt, Wolf Gero; Seino, K.; Furthmüller, J.; Bechstedt, F. (Journal of Computational Chemistry)

Calculation of surface optical properties: from qualitative understanding to quantitative predictions - Schmidt, Wolf Gero; Seino, K.; Hahn, P.H.; Bechstedt, F.; Lu, W.; Wang, S.; Bernholc, J. (Thin Solid Films)

Reflectance anisotropy of uracil covered Si(001) surfaces: Ab initio predictions - Seino, K.; Schmidt, Wolf Gero (Surface Science)

Semiconductor Optics in Photonic Crystal Structures - Meier, Torsten; Koch, Stephan W. (Photonic Crystals: Advances in Design, Fabrication, and Characterization)

Dynamics of short-time-scale energy relaxation of optical excitations due to electron-electron scattering in the presence of arbitrary disorder - Meier, Torsten; Varga, I.; Thomas, P.; Koch, S.W. (Physical Review B)
A nonequilibrium occupation distribution relaxes towards the Fermi-Dirac distribution due to electron-electron scattering even in finite Fermi systems. The dynamic evolution of this thermalization process assumed to result from an optical excitation is investigated numerically by solving a Boltzmann equation for the carrier populations using a one-dimensional disordered system. We focus on the short-time-scale behavior. The logarithmically long time scale associated with the glassy behavior of interacting electrons in disordered systems is not treated in our investigation. For weak disorder and short range interaction we recover the expected result that the relaxation rate is enhanced by disorder. For sufficiently strong disorder, however, we find an opposite trend due to the reduction of scattering probabilities originating from the strong localization of the single-particle states. Long-range interaction in this regime produces a similar effect. The relaxation rate is found to scale with the interaction strength, however, the interplay between the implicit and the explicit character of the interaction produces an anomalous exponent.

Theory for the nonlinear optical response of semiconductor surfaces: Application to the optical Stark effect and spectral oscillations of the Si(111)-(2x1) surface exciton - Meier, Torsten; Reichelt, Matthias; Koch, S.W.; Rohlfing, M. (Physical Review B)
A microscopic approach is presented to compute nonlinear optical properties of semiconductor surfaces. The method uses quasiparticle wave functions and dispersions obtained from ab initio band-structure theory as an input for Bloch equations which describe the optical properties. Excitonic effects in the linear absorption spectra of the Si(111)- (2×1) surface are obtained by integrating equations of motion. To demonstrate the applicability of the approach for analyzing nonlinear optical properties, ultrafast light-intensity-dependent absorption changes of the surface exciton are predicted. The numerical results discuss the optical Stark effect and spectral oscillations of the surface exciton which can both be observed in pump-probe experiments.

Signatures of biexcitons and triexcitons in coherent non-degenerate semiconductor optics - Meier, Torsten; Sieh, C.; Finger, E.; Stolz, W.; Rühle, W.W.; Koch, S.W.; Thomas, P. (physica status solidi (b))
Signatures of exciton and two-exciton states in semiconductor systems are investigated experimentally and theoretically. A set of quantum well samples with different well widths is studied using coherent excitation spectroscopy. The experimental results are analyzed using a microscopic model demonstrating the importance of biexciton correlations and disorder effects. Additional numerical investigations of absorption changes in small nanorings are employed to analyze optical transitions from two-exciton to three-exciton resonances.

Dynamics of short-time-scale energy relaxation of optical excitations due to electron-electron scattering in the presence of arbitrary disorder - Varga, Imre; Thomas, Peter; Meier, Torsten; Koch, Stephan W. (Physical Review B)
A nonequilibrium occupation distribution relaxes towards the Fermi-Dirac distribution due to electron-electron scattering even in finite Fermi systems. The dynamic evolution of this thermalization process assumed to result from an optical excitation is investigated numerically by solving a Boltzmann equation for the carrier populations using a one-dimensional disordered system. We focus on the short-time-scale behavior. The logarithmically long time scale associated with the glassy behavior of interacting electrons in disordered systems is not treated in our investigation. For weak disorder and short range interaction we recover the expected result that the relaxation rate is enhanced by disorder. For sufficiently strong disorder, however, we find an opposite trend due to the reduction of scattering probabilities originating from the strong localization of the single-particle states. Long-range interaction in this regime produces a similar effect. The relaxation rate is found to scale with the interaction strength, however, the interplay between the implicit and the explicit character of the interaction produces an anomalous exponent.

Electronic transport in a one-dimensional random array of scatterers - Meier, Torsten; Filinov, V.S.; Thomas, P.; Varga, I.; Bonitz, M.; Fortov, V.E; Koch, S.W. (Journal of Physics A: Mathematical and General)
The quantum dynamics of an ensemble of interacting electrons in an array of random scatterers is treated using a new numerical approach for the calculation of average values of quantum operators and time correlation functions in the Wigner representation. This approach combines both molecular dynamics and Monte Carlo methods and computes numerical traces and spectra of the relevant dynamical quantities such as momentum–momentum correlation functions and spatial dispersions. Considering, as an application, a system with fixed scatterers, the results clearly demonstrate that the many-particle interaction between the electrons can lead to an enhancement of the conductivity at intermediate densities.

Wigner approach to quantum dynamics simulations of the interacting carriers in disordered systems - Meier, Torsten; Filinov, V.; Thomas, P.; Bonitz, M.; Fortov, V.; Varga, I. (physica status solidi (b))
The new method for solving Wigner–Liouville's type equations and studying dynamics of quantum particles has been developed within the Wigner formulation of quantum statistical mechanics. This approach combines both molecular dynamics and Monte Carlo methods and computes traces and spectra of the relevant dynamical quantities. Considering, as an application, the quantum dynamics of an ensemble of interacting electrons in an array of random scatterers clearly demonstrates that the many-particle interaction between the electrons can lead to an enhancement of the electrical conductivity.

Semiconductor photonic-crystal structures: Optical spectra and carrier dynamics - Meier, Torsten

Microscopic theory for the nonlinear optical response of semiconductor surfaces: Application to the optical Stark effect of the Si(111)-(2x1) surface exciton - Meier, Torsten; Reichelt, Matthias; Koch, S.W.; Rohlfing, M. (physica status solidi (b))
A novel microscopic approach for computing nonlinear optical properties of semiconductor surfaces is outlined. The linear and nonlinear response of the Si(111)-(2×1) surface is studied using a combination of ab-initio band-structure theory and equation of motion technique. The usefulness of the method is shown by reproducing known excitonic effects in the linear differential reflectivity spectrum. To additionally demonstrate the applicability of the approach for the nonlinear regime, the nonlinear optical response in Stark effect configuration is examined.

Semiconductor excitons in photonic crystals - Meier, Torsten; Eichmann, R.; Pasenow, B.; Thomas, P.; Koch, S.W. (physica status solidi (b))
Optical properties of a semiconductor quantum well in the vicinity of a two-dimensional photonic crystal are investigated. Due to the periodic spatial modulation of the dielectric environment the effective Coulomb interaction potential exhibits the periodicity of the photonic crystal. As a consequence, the excitonic binding energy varies periodically by up to 50% depending on the spatial position of the exciton relative to the structured dielectric. The self image charge effects result in a position dependent shift of the single-particle bandgap such that the spectral position of the absorption spectrum also develops the periodicity of the photonic surrounding.

Semiconductor absorption in photonic crystals - Eichmann, R.; Pasenow, B.; Meier, Torsten; Stroucken, T.; Thomas, P.; Koch, S.W. (Applied Physics Letters)
Absorption spectra of semiconductor structures in photonic crystal environments are investigated numerically. It is shown that the periodic dielectric structuring changes the local optical and Coulomb interaction properties of semiconductor electron–hole excitations. The structurally induced modifications offer the possibility to design important aspects of the optoelectronic semiconductor properties.

Echos in Festkörpern - Meier, Torsten; Thomas, P. (Physik Journal)

Many-body Coulomb effects in the optical properties of semiconductor heterostructures - Meier, Torsten; Pasenow, B.; Thomas, P.; Koch, S.W. (Germany NIC Series, Vol. 20)

EfficientO(N2)method to solve the Bethe-Salpeter equation - Schmidt, Wolf Gero; Glutsch, S.; Hahn, P. H.; Bechstedt, F. (Physical Review B)

Chemisorption of pyrrole and polypyrrole on Si(001) - Seino, K.; Schmidt, Wolf Gero; Furthmüller, J.; Bechstedt, F. (Physical Review B)

Pyrrole (C4H4NH) and Polypyrrole Functionalized Silicon Surfaces Calculated from First Principles - Schmidt, Wolf Gero; Seino, K. (Surface Review and Letters)
The functionalization of the Si(001) surface by pyrrole and polypyrrole is investigated by means of first-principles pseudopotential calculations. We find dissociative reactions, leading to the partial fragmentation of the molecule, to be energetically most favored for pyrrole adsorption. The lowest-energy configuration for monolayer coverage is characterized by pyrrole rings bonded to the surface via Si–N linkage. In coexistence with adsorption geometries where both N and C are bonded to the surface, this structure accounts very well for the available experimental data. Chemisorption of pyrrole is found to effectively passivate the Si(001) surface, irrespective of the details of the adsorption geometry. The formation of well-ordered polypyrrole structures on Si(001) may require chemical modifications of the polypyrrole chains in order to account for the lattice mismatch.